2002
DOI: 10.1037/0735-7044.116.5.884
|View full text |Cite
|
Sign up to set email alerts
|

Double dissociation of function within the hippocampus: Spatial memory and hyponeophagia.

Abstract: Complete and dorsal hippocampal lesions impaired spatial performance on 2 working memory tasks: rewarded alternation on the T maze and matching to position in the water maze. In contrast, ventral hippocampal lesions had no effect on these tasks, even when task difficulty was increased by the introduction of delays. Ventral lesions did resemble complete lesions in reducing anxiety in 3 commonly used tests of anxiety (social interaction, plus-maze, and hyponeophagia). Dorsal lesions also appeared to be anxiolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
252
3
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(279 citation statements)
references
References 54 publications
19
252
3
2
Order By: Relevance
“…This hypothesis is consistent with the idea that the ventral hippocampus plays a more important role in unconditioned anxiety than the dorsal hippocampus, which is based on wide range of evidence Bannerman et al, 2004;Pentkowski, et al, 2006;Engin & Treit, 2007). More specifically, ventral cytotoxic lesions have been found to cause more pronounced anxiolytic effects than dorsal lesions on a variety of measures of innate anxiety, including elevated plus maze measures (Kjelstrup et al, 2002;Bannerman et al, 2002Bannerman et al, , 2004, and ventral infusion of the local anaesthetic lidocaine (a sodium channel blocker inactivating neurons and fibers of passage) significantly increased the proportion of open-arm entries on the elevated plus maze test, whereas dorsal lidocaine had no significant effect (Bertoglio et al, 2006). Moreover, ventral, but not dorsal, hippocampal muscimol reduced unconditioned fear, as assessed by the shock-probe burying test (McEown and Treit, 2010).…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…This hypothesis is consistent with the idea that the ventral hippocampus plays a more important role in unconditioned anxiety than the dorsal hippocampus, which is based on wide range of evidence Bannerman et al, 2004;Pentkowski, et al, 2006;Engin & Treit, 2007). More specifically, ventral cytotoxic lesions have been found to cause more pronounced anxiolytic effects than dorsal lesions on a variety of measures of innate anxiety, including elevated plus maze measures (Kjelstrup et al, 2002;Bannerman et al, 2002Bannerman et al, , 2004, and ventral infusion of the local anaesthetic lidocaine (a sodium channel blocker inactivating neurons and fibers of passage) significantly increased the proportion of open-arm entries on the elevated plus maze test, whereas dorsal lidocaine had no significant effect (Bertoglio et al, 2006). Moreover, ventral, but not dorsal, hippocampal muscimol reduced unconditioned fear, as assessed by the shock-probe burying test (McEown and Treit, 2010).…”
Section: Introductionsupporting
confidence: 87%
“…However, the effects of hippocampal manipulations on tests of anxiety, such as the elevated plus maze, show considerable variability across studies, depending on a variety of factors (see, for example, discussion in Bannerman et al, 2002). Two factors that may be particularly relevant concerning the present results are locomotor effects of the hippocampal manipulations and baseline anxiety levels.…”
Section: Distinct Effects Of Ventral and Dorsal Hippocampal Muscimolmentioning
confidence: 85%
See 2 more Smart Citations
“…Several lines of evidence have shown an important role of the hippocampus in WM. For example, lesion studies showed that rats with complete or dorsal hippocampus lesions had impaired WM (Bannerman et al, 2002). In human patients, medial temporal lobe amnesia was linked to severely impaired WM at 8 s delays, suggesting that the hippocampus per se is critical for accurate conjunction WM (Olson et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%